2021
DOI: 10.1177/14757257211037149
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in psychology: How can we enable psychology students to accept and use artificial intelligence?

Abstract: Psychologists with their expertise in statistics and regarding human perception and behavior can contribute valuable insights to the development of innovative and useful artificial intelligence (AI) systems. Therefore, we need to raise attention and curiosity for AI and foster the willingness to engage with it among psychology students. This requires identifying approaches to integrate a general understanding of AI technology into formal psychological training and education. This study investigated to what ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 77 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…By differentiating between specific tool understanding and more general cognitive technology readiness, the current study moves beyond previous research that focused on the role of general AI knowledge in predicting general usage intention (Gado et al, 2022). The mediation analyses revealed that none of the three UTAUT variables mediate the relationship between tool understanding/cognitive technology readiness with the intention to use the feedback tool.…”
Section: Principal Findingsmentioning
confidence: 71%
See 4 more Smart Citations
“…By differentiating between specific tool understanding and more general cognitive technology readiness, the current study moves beyond previous research that focused on the role of general AI knowledge in predicting general usage intention (Gado et al, 2022). The mediation analyses revealed that none of the three UTAUT variables mediate the relationship between tool understanding/cognitive technology readiness with the intention to use the feedback tool.…”
Section: Principal Findingsmentioning
confidence: 71%
“…Furthermore, Tran et al (2021) identified social influence as the only significant predictor of the intention to use AI-CDSSs among undergraduate medical students. Gado et al (2022) found support for direct effects of perceived usefulness, AI knowledge, and perceived social norms on the intention to use AI, as well as indirect effects of perceived ease of use on usage intention via positive attitudes towards AI in a sample of psychology students. This consistent link between social influence and AI usage intentions found in studies using student samples may be explained by the greater susceptibility of students to the influence of peers and prospective employers (Hurst & Good, 2009).…”
Section: Principal Findingsmentioning
confidence: 86%
See 3 more Smart Citations